2007
DOI: 10.2310/7070.2007.0031
|View full text |Cite
|
Sign up to set email alerts
|

Rounding of the Inferior Rectus Muscle as an Indication of Orbital Floor Fracture with Periorbital Disruption

Abstract: IObjective: To determine if rounding of the inferior rectus muscle on coronal computed tomographic (CT) scans predicts disruption of the periorbita in orbital floor fractures and therefore predicts delayed enophthalmos.Design: Cadaveric study with CT scan analysis. I Setting: Cadaveric laboratory and CT scanner at a tertiary care hospital in London, Ontario.Methods: Each orbit of each cadaveric head was randomly assigned to have either intact or disrupted periorbita. Progressively larger orbital floor fracture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…29 Some authors have advocated evaluating this by examining the shape of the inferior rectus by means of coronal computed tomographic scans. 30,31 It is felt that rounding of the relatively flat inferior rectus is an indication of loss of ligamentous support and, subsequently, a higher likelihood of enophthalmos developing (Fig. 4).…”
Section: Clinical Managementmentioning
confidence: 97%
“…29 Some authors have advocated evaluating this by examining the shape of the inferior rectus by means of coronal computed tomographic scans. 30,31 It is felt that rounding of the relatively flat inferior rectus is an indication of loss of ligamentous support and, subsequently, a higher likelihood of enophthalmos developing (Fig. 4).…”
Section: Clinical Managementmentioning
confidence: 97%
“…Levine et al proposed that soft tissue edema alone or together with intramuscular and perimuscular hemorrhage could cause the shape of the inferior rectus muscle to change from elliptical to round on coronal CT. 21 Alternatively, others have hypothesized that rounding occurs because of disruption of orbital periosteum, which subsequently leads to periorbital herniation into the maxillary sinus. 5,8,9 These opposing theories were tested by Banerjee et al in a cadaveric study. 8 They showed that progressively larger orbital floor defects resulted in ptosis of orbital soft tissue into the maxillary sinus.…”
Section: Rounding Of the Inferior Rectus Musclementioning
confidence: 99%
“…This finding has been shown to be predictive of post operative enophthalmos. 55,56 Moreover, Matic et al have shown that a heighttowidth ratio greater than 1.00 in the inferior rectus muscle is predictive of late enophthalmos but not per sistent diplopia. 57…”
Section: Enophthalmosmentioning
confidence: 99%